Inhibition of MEG3 ameliorates cardiomyocyte apoptosis and autophagy by regulating the expression of miRNA-129-5p in a mouse model of heart failure - Shan Mi; Feng Huang; Mingli Jiao; Zhuang Qian; Mingming Han; Zheng Miao; Heqin Zhan (Taylor & Francis Group, 2023)
ABSTRACTThe long non-coding RNA, maternally expressed gene 3 (MEG3), are involved in myocardial fibrosis and compensatory hypertrophy, but its role on cardiomyocyte apoptosis and autophagy in heart failure (HF) remains unclear. The aim of this study was to investigate the effect of MEG3 on cardiomyocyte apoptosis and autophagy and the underlying mechanism. A mouse model of HF was established by subcutaneous injection of isoproterenol (ISO) for 14 days, and an in vitro oxidative stress injury model was replicated with H2O2 for 6 h. SiRNA-MEG3 was administered in mice and in vitro cardiomyocytes to knock down MEG3 expression. Our results showed that cardiac silencing of MEG3 can significantly ameliorate ISO-induced cardiac dysfunction, hypertrophy, oxidative stress, apoptosis, excessive autophagy and fibrosis induced by ISO. In addition, inhibition of MEG3 attenuated H2O2-induced cardiomyocyte oxidative stress, apoptosis and autophagy in vitro. Downregulation of MEG3 significantly inhibited excessive cardiomyocyte apoptosis and autophagy induced by ISO and H2O2 through miRNA-129-5p/ATG14/Akt signaling pathways, and reduced H2O2-induced cardiomyocyte apoptosis by inhibiting autophagy. In conclusion, inhibition of MEG3 ameliorates the maladaptive cardiac remodeling induced by ISO, probably by targeting the miRNA-129-5p/ATG14/Akt signaling pathway and may provide a tool for pharmaceutical intervention.